Kesesuaian Kegiatan Dana Alokasi Khusus (DAK) Pariwisata dan Permasalahan Pariwisata di Indonesia - Joko Tri Haryanto (Matra Pembaruan: Jurnal Inovasi Kebijakan, 2019)
Today's, tourism industry has developed into an important industry and has a significant impact on national development efforts through state revenuesas well as in the regions. Indonesia itself, has long been known as one of the world tourism destination. Various forms and types of tourism exist and grow in Indonesia. Therefore, since 2008, the government continues to develop the tourism sector as one of the priority sectors in national development, including the development program of 10 New Tourism Destinations beside Bali in 2015. Government commitment is also realized in the aspect of funding, through the allocation of APBN especially Transfer to Region in the DAK Physical on Tourism sector. To be beneficial, the allocation is certainly expected to be right on target. For this reason, an analysis of the conformity between the allocation of DAK Physical on Tourism Sector and the real problems in the national tourism sector is needed. This study then tried to answer these needs by using the menu evaluation analysis method and the DAK Physicalon Tourism allocation activities. From the results of the analysis since 2016, in general it can be said that the allocation of Physical DAK in Tourism has been aligned with the real problems in the national tourism sector, especially related to indicators of security and safety, health and hygiene, ICT readiness and tourism infrastructure services. The Physical DAK Allocation of Tourism from 2016-2018 still has not touched the indicator of the problem of environmental resilience which should be considered in the future.